Analisis Perhitungan Pajak Pertambahan Nilai Dan Pajak Penghasilan Pasal 21 Terhadap Hutang Pajak Pada PT Higashifuji Indonesia - Annisa Hayatun Nufus; Bambang Santoso; Zulmita Zulmita (Cakrawala Akuntansi & Manajemen, 2023)
One of the Largest Revenues in Indonesia is the Tax Sector. Tax is a taxpayer's contribution which is applied to every taxpayer on the tax object received and the results are submitted to the State, and do not receive direct compensation and are used to finance the development of the State. This study aims to determine the calculation of Value Added Tax and Income Tax Article 21 on the Tax Payable of PT Higashifuji Indonesia. The author limits the limitation of the problem, namely Based on the background of the above discussion, the author limits it to those related to VAT and PPh Article 21 of PT Higashifuji Indonesia. In the calculation of Value Added Tax there is an error in entering the selling unit price on the Output Tax Invoice and PPh article 21, there is an error and miscalculation of PPh 21 due to allowances that have not been entered by the company and incorrectly inputting employee status. This study was conducted to determine the implementation of the reporting of Value Added Tax and Income Tax Article 21 conducted at PT Higashifuji Indonesia. Sources of data used in this study were taken from financial statements regarding tax payments in the company. Technical data collection through observation, interviews, and documentation. Data analysis methods used are quantitative and descriptive methods. After studying and discussing the Value Added Tax and Income Tax Article 21, it can be concluded that there is a difference between the calculation of the company and the calculation of the researcher. From the research results obtained, the value added tax in 2019 then the tax debt that must be paid is Rp. 20,950,500.00, while the calculation of income taxarticle 21 in 2019 the tax payable to be paid is Rp. 9,336,802.90.